Computational, Kinetics, and Corrosion Protection Aspects of Electrodeposited Poly(Salicylic Acid) Coatings as a Corrosion Inhibitor for Mild Steel - Ghada M. Abd El-Hafeez; Mohamed M. El-Rabeie; El Hassane Anouar; Moustapha E. Moustapha; Amany M. A. Osman; Zeinab R. Farag (Journal of Chemistry)
Poly(salicylic acid) PSA has been electrochemically deposited onto a Pt electrode. The kinetics of the polymerization reaction has been studied. The polymer structure was confirmed and characterized using IR spectroscopy, XRD, SEM, and TGA analysis. The deposited PSA was then collected from the Pt surface and tested as a corrosion inhibitor for a mild steel electrode in an aqueous medium of 1 M sulfuric acid. The corrosion behavior was then evaluated using potentiodynamic polarization and electrochemical impedance spectroscopy (EIS). Corrosion measurements showed that the inhibition efficiency of 20, 50, and 100 ppm of PSA was 33, 57, and 74%, respectively. The inhibition mechanism was proved using adsorption isotherms as well as quantum calculations. The inhibition of the corrosion process was due to the adsorption of PSA on the steel surface, which was found to comply with the Langmuir adsorption isotherm.